Reported speech as a strategy to organize the news - Sant’Anna, Vera Lúcia de Albuquerque (The ESPecialist, 2012)
This article presents part of my doctoral dissertation, which focused on the observation of the process of discursive constitution of the world of work in news from the newspapers Clarín and Folha de S. Paulo, in the scope of Mercosul. Tje article is restricted to the exposition of the criteria that guided the study of reported speech (RS) as the main organiser of the news, a discursive genre whose enunciative basis is the tension between informing and expressing opinion. The option for the study of RS springs from my interest in verifying the distance between those two acts, as informing has been considered responsible for the idea of objectivity that sustains the characterization of the news text. It was possible to conclude that, in the constitution proposal of a continuum of occurrences, the notion of “narrated” speech stands out as one of the basic strategies for the institution of the idea of information objectivity, which derives from the enunciative perspective of the enunciator/journalist.